2016
DOI: 10.1038/bjc.2016.401
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of CD44-positive cancer stem-like cells at the invasive front of gastric cancer

Abstract: Background:The invasive tumour front may provide prognostic information. We examined the relationship between the presence of cancer stem cells (CSCs) at the invasive tumour front and prognosis in gastric cancer (GC).Methods:CD44 is a CSC marker; accordingly, CD44 standard (CD44s), CD44 variant-6 (CD44v6), and CD44 variant-9 (CD44v9) expression were examined in 123 resected primary GCs and the clinical significance of CSCs at the invasive tumour front was analysed.Results:Thirteen (10.6%), 79 (64.2%), and 47 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…In the case of the antibody-conjugated NPs, however, an inverse trend was observed, with NPs conjugated with a smaller amount of targeting agent being more effective than the ones conjugated with a larger amount of antibody. This observation is quite relevant as it confirms earlier observations that small amounts of antibodies are sufficient to obtain a good targeting and delivery efficiency [34,35]. When the density of antibody on the particles surface is increased, they may interfere with each other, decreasing their effectiveness.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In the case of the antibody-conjugated NPs, however, an inverse trend was observed, with NPs conjugated with a smaller amount of targeting agent being more effective than the ones conjugated with a larger amount of antibody. This observation is quite relevant as it confirms earlier observations that small amounts of antibodies are sufficient to obtain a good targeting and delivery efficiency [34,35]. When the density of antibody on the particles surface is increased, they may interfere with each other, decreasing their effectiveness.…”
Section: Resultssupporting
confidence: 86%
“…One of the most known markers of CSCs is the CD44v6 isoform, and its metastasis promoting activity was first described in 1991 [32]. The CD44v6 isoform is overexpressed in several CSCs (e.g., in colorectal and pancreatic cancers [33], gastric cancer [34], and ovarian cancer [35]), thus representing an ideal candidate for targeted cancer therapies.Moreover, CD44 is the major hyaluronan receptor [36,37]. Hyaluronic acid (HA) is a natural, biodegradable, non-immunogenic, and water-soluble polysaccharide present in the extracellular matrix and synovial fluids [38][39][40][41].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CD44v9 expression is significantly associated with poor prognosis of patients with gastric, bladder, and liver cancers, as well as other cancers . Although most studies of CD44v9 examined its expression according to the intensity of staining or the proportion of CD44v9‐positive cells in whole tumor sections, several studies have reported levels of CD44v9 expression at the TIF . For example, in non‐muscle invasive bladder cancer expression of CD44v9 is localized to the TIF .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in non‐muscle invasive bladder cancer expression of CD44v9 is localized to the TIF . In gastric cancer, expression of CD44v6 and CD44v9 at the TIF is more strongly associated with poor prognosis than expression in whole tumor sections …”
Section: Discussionmentioning
confidence: 99%